PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PELAYANAN TANAH DI KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Amanda, Calvin; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The background for writing this thesis is the reality in the field, it can be seen that the services provided by service officers do not fully reflect quality services and are still unable to provide excellent service to the community. The purpose of this thesis research is to find out the application of the principles of good governance in land services in Sentajo Raya District, Kuantan Singingi Regency in 2021. Researchers use a qualitative approach. This type of research is descriptive. The research location is in Sentajo Raya District, Kuantan Singingi Regency. With the type and source of data In this study the primary data is in the form of interviews and observations conducted by researchers and secondary data is supporting data from the main data which consists of report data, as well as Profile documents, organizational structure, and tasks related to land services in the Office Head of Sentajo Raya Subdistrict, Kuantan Singingi Regency. Data collection techniques used interviews and documentation. While data analysis was performed using qualitative analysis. Based on the results of the research and discussion, it can be concluded that the application of the principles of good governance in land services in Sentajo Raya sub-district, Kuantan Singingi district, it is known that the accountability indicators look quite good because in terms of the speed of service time, it is not in accordance with the service SOP. The transparency indicator is still not optimal because many people do not know the flow of services, especially land services at the Sentajo Raya sub-district office. In the openness indicator, this can be seen from the Sentajo Raya sub-district office does not have a public complaint facility, so if the community has a problem, there is no complaint service. Meanwhile, the indicators of the rule of law have not been maximized, which can be seen from the lack of discipline of officers who are not in place during working hours but there are no sanctions given to these employees. Keywords : Keywords: Principles of Good Governance, Land Services, and District Offices